On the role of mindfulness and compassion skills in students' coping, well‐being, and development across the transition to college: A conceptual analysis. (8th January 2019) - Dvořáková, Kamila; Greenberg, Mark T.; Roeser, Robert W.
Abstract: In this paper, we aim to integrate the current conceptual approaches to stress and coping processes during the college transition with the potential role of mindfulness and compassion (MC) skills on students' well‐being and development. First, we provide an overview of the issues and challenges emerging adults are facing during the transition to college, drawing on the revised version of the transactional stress model by Lazarus and Folkman (1984). Second, we introduce a conceptual model of adaptive stress and coping processes enhanced by MC skills to positively impact the appraisal and coping resources and emerging adults' mental health. Specifically, MC skills may play an important role in promoting a healthy stress response by strengthening emerging adults' socioemotional competencies and supporting the development of adaptive appraisal and coping resources, including processes antecedent and consequent to a coping encounter. In particular, MC skills were hypothesized to enhance (a) preparedness to cope, (b) productive stress response through adaptive appraisals and skillful deployment of coping resources, and (c) healthy postcoping reflections. Therefore, MC skills may be a useful preventive tool to strengthen emerging adults' ability to adjust to a new academic environment and fulfil the developmental tasks of this period.